Economic analysis of fish production using different feed types practiced in Dhanusha district, Nepal - Subedi, Pritee; Pandit, Narayan Prasad; Mahato, Naresh Kumar; Karki, Mahesh; Uprety, Anupam (Journal of Agriculture and Natural Resources, 2019)
A study on the economic analysis of fish production using different feed types practiced in Dhanusha district was conducted in 2018. Out of 600 fish farmers, sixty fish farmers(10%) from the Fish Superzone region i.e. Janakpur sub-metropolitan city, Bideh municipality, Sahidnagar municipality, Kamala municipality, Hanspur municipality, Janaknandani rural municipality and Aaurahi rural municipality, selected using simple random sampling, were surveyed using semi-structured questionnaire. The study revealed that locally formulated mash feed was commonly used feed type in which rice bran and mustard oil cake (RB+MOC) was the principle feed ingredient. 55% of the farmers used rice bran and mustard oil cake (RB+MOC), 20% used rice bran, mustard oil cake and soybean (RB+MOC+SOB), 10% used rice bran, mustard oil cake and fish meal (RB+MOC+FM) and 15% farmers mineral and vitamin (RB+MOC+MIN/VIT) in their feed formulation. The productivity of the fish production in feed type RB+MOC+SOB (3.41±1.02) was significantly higher than other feed type. The total variable cost per ha (5.23±2.11) was found significantly(p<0.05) higher in feed type RB+MOC+SOB. Similarly, gross margin (4.44±2.74) received by farmers of feed type RB+MOC+SOB was also significantly high(p<0.05). The Benefit: Cost (B:C) ratio of the study area was found to be 1.69, high being of feed type RB+MOC+SOB(1.84) compared to others. The feed type RB+MOC+SOB is seen as a economically profitable one in the study area because of the high productivity, profit and B:C ratio. High feed cost was the major problem followed by the unavailability of feed. Fish farming can be a profitable business in Dhanusha with large opportunity to increase the fish production with increasing protein sources in the feed used. Farmers should be provided sufficient information, trainings and be encouraged to incorporate the protein rich sources like soybean and fish meal in the feed prepared to increase the productivity and ultimately return.